Fundamental determinants of the long run real exchange rate: The case of Norway - Hilde C. Bjørnland; Håvard Hungnes (University of Oslo, Department of Economics, 2002)
Modelling the Norwegian exchange rate against a basket of currencies, we find a robust long-term link between the real exchange rate and real interest differential that is consistent with purchasing power parity (PPP) and uncovered interest parity (UIP). However, PPP alone is rejected. These findings are confirmed focusing on the Norwegian bilateral exchange rate with Germany and (possibly) Sweden, but rejected against the UK and the US. We argue that rejection of bilateral relationships may result from idiosyncratic shocks in the different countries that may be negligible when modelling against a basket of currencies.
Keywords: C32; F31; 330; Purchasing power parity; uncovered interest parity; cointegration VAR; Kaufkraft; Zinsparität; Kointegration; Schweden; Norwegen; Deutschland; Großbritannien; USA